Mobility performance of a new traffic decentralization qos admission strategy - Georgios S. Paschos; Efstathios Vagenas; Stavros A. Kotsopoulos (Communications - Scientific letters of the University of Zilina, 2004)
This paper proposes a new Admission Control strategy with Quality of Service (QoS) preservation for GSM networks. System initiated handover calls are used in the central cell in order to decentralize the traffic and redistribute it throughout the whole cluster. Although the channels and the cell size are fixed, the system behaves as if it had the 3G feature called soft capacity. The mobility characteristics of the users are investigated. Low speed and high speed moving users are used as input in the system and the effect of mobility on the proposed algorithm is extracted. Simulation results show that the proposed Admission Strategy is flexible, efficient and very useful in situations when the traffic is centralized.